Debt To Equity Ratio (DER) Terhadap Harga Saham Pada PT Tiga Pilar Sejahtera Food Tbk Periode 2010-2017 - Vina Adriana; Rita Mutoharoh (LPPM POLITEKNIK LP3I BANDUNG, 2019)
This research aimed to determine: (1) Debt to Equity Ratio of PT. Tiga Pilar Sejahtera Food, Tbk. period 2010-2017. (2) The influence of Debt to Equity Ratio to stock price of PT. Tiga Pilar Sejahtera Food, Tbk. period 2010-2017. The population of this research is the financial statements of PT. Tiga Pilar Sejahtera Food, Tbk. for 8 years that is 2010-2017. The method used in this research is quantitative methods. The analysis technique used is descriptive statistics, simple linear regression, classical assumption test, and partial test t. As for calculations using IBM SPSS Statistics 23. The result of this study were: (1) Debt to Equity Ratio has a negative and significant effect on stock prices with the value of Sig. 0.002 (0.002 <0.05) and tcount < ttable 2.042. The conclusions of this study are: (1) Development conditions of Debt to Equity Ratio PT. Tiga Pilar Sejahtera Food, Tbk. The 2010-2017 period experienced fluctuations. (2) Debt to Equity Ratio partially has a negative and significant effect on stock prices of PT. Tiga Pilar Sejahtera Food, Tbk. period 2010-2017.